ISO 9001 Performance: A Holistic and Mixed-Method Analysis - Alcina A. de SENA PORTUGAL DIAS; Iñaki Heras SAIZARBITORIA (Revista de Management Comparat International)
Purpose – The aim of this paper is to analyse the impact of the ISO 9001 Standard on organizational performance from a holistic theoretical perspective, using a mixedmethod analysis. More specifically, the qualitative study considers the impact of the adoption of ISO 9001 on the general performance of certified companies. The quantitative study analysed the effect of ISO 9001 on productivity, business value and increase on sales. Design/methodology/approach – A holistic and integrative theoretical approach was adopted, bringing together aspects of the Contingency Theory, the Institutional Theory and the Resources-Based View (RBV). This theoretical perspective was used in a broad empirical study, using a mixed-method analysis combining the use of qualitative and quantitative methods. The study focused on Portuguese companies from different sectors of activity. Findings – The qualitative study confirmed that ISO 9001 was a demand from the market thus conferring a competitive advantage to organizations and it was also clear that without ISO 9001 these would not enter the market. From the quantitative perspective, data obtained indicate a correlation between ISO 9001 and the size of the organizations. Nevertheless, the analysis also showed that some relationships between ISO 9001 and improved performance were not significant and mostly it seems they depend on the sector of activity considered. Research limitations/implications – This study is limited to the consideration of just two sectors of activity and a single geographical location. Therefore, the results cannot be generalized. In the case of the qualitative study, the respondent’s self-reporting bias should be considered. Some extension of the scope of analysis to other sectors and an international sample would be advisable in order to compare results. Another limitation may be the possible selection bias introduced when organizations decide to take part or not. Practical implications – The practical implications of this study relate to conclusions about top management involvement and about the fulfillment of ISO 9001 procedures. These are elements that organizations should consider from this study. These practical implications are in line with other similar studies. Originality/value – This paper is a relevant contribution to the state of the art through the use of the holistic theoretical perspective and the mixed-method approach.